Efficiency Analysis of Financial Management Administration of ABC Hospital using Financial Ratio Analysis Method - Jonny Jonny (Bina Nusantara University, 2016)
This paper evaluated the financial performance of ABC hospital within the period of 2012 to 2013. To overcome the problems faced by the hospital related to how to measure and presented its financial performance in which financial ratio analysis was undertaken. These financial ratios were employed to measure the liquidity, assets utilization, long-term solvency and profitability of the hospital. This analysis was conducted in order to prove whether the hospital has been managed efficiently or not in accordance to Indonesian Hospital Quality Accreditation as stated in its clause on Administration Standard No. 5 Parameter No. 3 that the hospital financial management shall be conducted in appropriate way in order to guarantee its operation efficiently. The result showed that overall financial performance of ABC hospital increased considerably in those two years of the analysis. A significant change was occurred on its solvency ratio which was decreased from -2% to -8%, indicating its loose dependency due to its founder’s strong financial support. Therefore, based on this favorable result, the hospital was regarded to have efficient hospital management and thus, together with other standard fulfillment, it was accredited by Indonesian Health Ministry.